Transfers, and the Challenges for Social Protection Systems in the People's Republic of China - Qiulin Chen; Karen Eggleston; Ling Li (Asian Development Bank (ADB), 2011)
The transition in the People's Republic of China from a centrally planned economy to a market-based economy is widely acclaimed for leading to unprecedented economic growth, but there is a growing awareness of the social strains accompanying that growth such as the lagging development of the social protection system as the population ages. Using estimates from the National Transfer Accounts database, we describe changes in life cycle public transfers; interhousehold transfers; and intrahousehold transfers for education, health care, and other support; and discuss the main challenges that demographic change poses for the pension and health care systems. Demographic change and its interaction with family behavior and social policies will strongly shape both future economic growth - through savings and investment decisions, labor supply and productivity - and the sustainability of social support systems.
hdl:11540/1994
Keywords: 330; Bevölkerungsentwicklung; Generationengerechtigkeit; Soziale Sicherheit; Sozialpolitik; China